Gambaran Klinikopatologi Karsinoma Laring di Laboatorium Patologi Anatomi RSUP. Dr. M. Djamil Padang Tahun 2018 -2021 - Fikri Akbar; Ade Asyari; Netti Suharti (Jurnal Anestesi, 2025)
Laryngeal carcinoma is a cancer of the larynx that attacks the normal epithelium of the larynx. This carcinoma is the second most common type of head and neck epithelial malignancy in the world and the second most common in the respiratory tract after lung cancer. Carcinoma of the larynx has non-specific clinical manifestations, causing delayed early detection, thus affecting the management and prognosis of patients. This study aimed to determined the frequency distribution of laryngeal carcinoma patients based on gender, age, clinical manifestations, location, histopathological type, degree of differentiation. This research is a categorical descriptive study. The study sample was patients diagnosed by an ENT doctor as a primary malignancy of laryngeal carcinoma with confirmation from histopathological examination.The results of this study showed that the majority of laryngeal carcinoma patients were male (94%), the most age group was 59-65 years old (30.61%), the most common clinical manifestation was hoarseness (42.8%), The most common tumor location was in the glottis (92%), the most common histopathological features were squamous cell carcinoma (98%), and the highest degree of differentiation was moderate differentiation (36.73%). The majority of laryngeal carcinoma patients are men with an age range of 59-65 years. The most clinical manifestations were hoarseness, the most common tumor location was in the glottis, the most histopathological features were squamous cell carcinoma, and the highest degree of differentiation was moderate differentiation.